Opt-out testing for HIV: perspectives from a high prevalence community in south-east England, UK. (April 2013) - Pollard, A; Llewellyn, C; Smith, H; Richardson, D; Fisher, M
Summary: Peoples' perspectives and attitudes towards being offered opt-out HIV testing were explored in a geographical area of high HIV prevalence. Users ( n = 31) of sexually transmitted infection (STI) testing services took part in community focus groups in the south-east of England, UK. There was broad support for opt-out HIV testing based on public health and individual health benefits. For this sample, opt-out HIV testing when registering with a general practice surgery and on elective or emergency admission to a general hospital was acceptable, although there were concerns about the rigour of informed consent. Heterosexual participants' criticism of people from higher prevalence groups for HIV declining tests, while maintaining their own right to opt-out, suggested that attitudes towards testing may be influenced by levels of perceived risk. Innovations in HIV testing policies to increase testing rates will benefit from an acknowledgement of the different meanings that testing has.